Transmedia contents created around Spanish television series in 2013: typology, analysis, overview and trends (Communication & Society, 2014)
This article analyses the transmedia contents created around 33 Spanish television series broadcast in 2013 by national and regional TV networks. The article reviews the TV series’ official websites, in which the transmedia contents are made available, and organises the wide variety of transmedia formats created around the sample of TV series, based on the different touchpoint categories, which refer to any content or strategy that allow viewers to engage with a television brand through other media and platforms. The results indicate that there is an overwhelming presence of TV contents that are repackaged or adapted to the new medium or platform and that there is still a lack of transmedia expansion through contents that are actually new, differentiated across media, and narratively relevant.